Ethical perspective of the cadaver researches [Kadavralar üzerinde yapilan araştirmalarin etik boyutu] - (:unkn) unknown (My University, 2004)
It is known that after Nuremberg Trials, ethical perspective of the human experimentations has become much more important. Although there are a lot of publications about the ethics of human experimentations, there exists several review articles on researches conducted on cadavers. The usage of cadaver in medical researches has always been very difficult. Main problem mostly focus on to provide the cadaver. Principles of the beneficience, autonomy and justice are seem to be the main principles that we should care about; but the principle of the respect to the autonomy seems much more important for cadaver researches and provision of cadavers. The principle of autonomy -that is important for the human experimentations- should be cared about the cadaver researches too. Today, although to provide cadaver for medical education or research purposes is very difficult; it is very important to behave respectful to the decision of the people who donates their body for medical purposes after their death.